Analisis Hubungan antara Kinerja Keuangan, Ukuran Perusahaan, dan Kebijakan Dividen dalam Mengoptimalkan Harga Saham - Muchtadin, Muchtadin (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
In the dynamic world of capital markets, companies do not only focus on their financial performance. Company size and dividend policy are also critical elements in shaping investor perceptions and driving share prices. This research has the main objective of investigating and analyzing how financial performance, company size, and dividend policy can jointly contribute to the optimization of a company's share price. This research uses a statistical analysis approach by collecting and analyzing financial data and company shares. The method used is a quantitative descriptive method. The total research population was 88 companies, while the total research sample was 20 companies. This approach allows research to identify and quantify the statistical significance of each observed relationship. The research results show that strong financial performance, optimal company size, and appropriate dividend policy have a positive impact on increasing company share prices. This means that companies that succeed in managing these factors well tend to have better stock performance in the capital market.